A brief mindfulness intervention reduces the tendency to endorse negative Black stereotypes. Issue 2 (11th October 2022) - Ingold, Kimberly; Lueke, Adam
Abstract: Stress has been implicated in causing people to be more reliant on the use of stereotypes. Mindfulness has been shown to reduce stress, in addition to its promise as a method to reduce negative judgments of members from historically disadvantaged groups. The current study examined the possibility that a brief mindfulness meditation could reduce the reliance on negative Black stereotypes. Endorsement of White stereotypes was also examined. Furthermore, we investigated whether mindfulness could buffer against the tendency of stress to increase reliance on these stereotypes. Participants totaled 160 and were recruited from Mturk and a large Midwestern university. They listened to either a 10‐min mindfulness or control audio tape, then completed either a stressful task or control task before answering questions to gauge reliance on stereotypes. Results indicated that the mindfulness condition significantly reduced the tendency to rely on Black stereotypes in comparison with the control condition. Participants in the stress condition increased reliance on these stereotypes, but mindfulness did not buffer against this effect. Interestingly, mindfulness did not affect the tendency to endorse negative stereotypes about Whites, which tended to be higher than negative Black stereotypes. These results suggest that mindfulness may be particularly effective in reducing the reliance on negative Black stereotypes in neutral conditions, but perhaps not under stressful conditions. Implications and future directions are discussed.